Infrastructural events? Flood disaster, narratives and framing under hazardous urbanisation. (May 2022) - Coates, Robert
Abstract: 'The river was moved too close to my house!' declared a soon-to-be-displaced resident following flood disaster in Brazil. Infrastructural engineering decades earlier had changed the river's course and led to the flooding of his home, yet the state now blamed a rainstorm for causing the disaster. The narrative of a natural event provided the pretext for urban governance based around evictions and further rounds of infrastructural engineering, nominally aimed at pre-empting a dangerous climate future. The paper takes the circumstances of this case to trigger a conceptual discussion on governance of the disaster event, narratives, and the promise of infrastructures to mitigate alarming urban futures. I draw on urban political ecology, the sociology of the event, and recent social studies of infrastructure, while also questioning understandings of eventful nature in the post-human turn. Tackling urban disaster risk, it is argued, depends on a political reframing of disasters as infrastructural events. This is a reflexive process that challenges how risks are produced through capitalist urbanisation, with the aim of making this longer temporality eventful for social change. A focus on politicised infrastructures reveals and disrupts dominant natural hazard narratives that remain integral to hazardous urban expansion.